Influence of thyroid states on the local effects induced by Bothrops envenoming. (August 2015) - Saraiva, Raquel Moreira; Caldas, Adriele Souza; Rodriguez, Tania Tavares; Casais-e-Silva, Luciana Lyra
Abstract: Bothrops leucurus venom causes significant local effects, such as necrosis, pain, hemorrhage and edema. These effects are important because of their high frequency and severity. The treatment of these local effects is not simple because of their quick triggering and a variety of components that induce these effects. Myonecrosis, dermonecrosis and edema are primarily caused by the action of hemorrhagins and myotoxins. A number of investigators have demonstrated the influence of thyroid hormones on inflammatory processes, particularly on wound healing. We investigated the edematogenic, hemorrhagic and necrotic activity of the B. leucurus venom in the hypothyroid, hyperthyroid and euthyroid of rats. The CK (creatine kinase) plasma level decreased in the animals in a hypothyroid state. The hypothyroid condition also significantly reduced the hemorrhagic and dermonecrotic area compared to the euthyroidism and hyperthyroidism states. It also mitigated the rat paw edema compared to that found in the euthyroid and hyperthyroid animals. The hyperthyroid animals showed no significant differences in the three treatments compared to the euthyroid animals. Our results suggest that the triggering of local effects induced by envenomation by B. leucurus is attenuated in hypothyroid animals, possibly by the effect of hypothyroidism on the immune system and blood flow. Highlights: This is the first study about thyroid hormone state and snake envenomation. We study influence of thyroid hormone state on local effect on Bothrops envenoming. It will contribute to understand the pathogenesis of local effects by Bothrops venom.